2016
DOI: 10.1039/c6nr00795c
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted photoluminescence fine-tuning of gold nanodots through free radical-mediated ligand-assembly

Abstract: In this study, we have developed a simple photoassisted ligand assembly to fine-tune the photoluminescence (PL) of (11-mercaptoundecyl)-N,N,N-trimethylammonium bromide-capped gold nanodots (11-MUTAB-Au NDs). The 11-MUTAB-Au NDs (size: ca. 1.8 nm), obtained from the reaction of gold nanoparticles (ca. 3 nm) and 11-MUTAB, exhibited weak, near-infrared (NIR) PL at 700 nm with a quantum yield (QY) of 0.37% upon excitation at 365 nm. The PL QY of the Au NDs increased to 11.43% after reaction with 11-mercaptoundecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(98 reference statements)
3
5
0
Order By: Relevance
“…Recently, some studies have revealed the charge, density, and rigidity of the Au­(I)–thiolate shell plays a crucial role in determining the QY of Au–thiolate NCs. Those Au–thiolate NCs having highly dense thiolated ligands and QY > 10% mostly are emitted at 600–700 nm, ,,, consistent with our Au NCs/–[Cys–Au­(I)] n – supramolecules (630 nm). Compared to the employed organic solvent, mixed ligands, ligand exchange, host–guest recognition, ultrasound- or light irradiation-treatment to obtain dense thiolated ligands on Au NCs for boosting the QY of Au NCs, ,,, our one-pot synthesis of highly photoluminescent Au NCs/–[Cys–Au­(I)] n – supramolecules is relatively simple and straightforward.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Recently, some studies have revealed the charge, density, and rigidity of the Au­(I)–thiolate shell plays a crucial role in determining the QY of Au–thiolate NCs. Those Au–thiolate NCs having highly dense thiolated ligands and QY > 10% mostly are emitted at 600–700 nm, ,,, consistent with our Au NCs/–[Cys–Au­(I)] n – supramolecules (630 nm). Compared to the employed organic solvent, mixed ligands, ligand exchange, host–guest recognition, ultrasound- or light irradiation-treatment to obtain dense thiolated ligands on Au NCs for boosting the QY of Au NCs, ,,, our one-pot synthesis of highly photoluminescent Au NCs/–[Cys–Au­(I)] n – supramolecules is relatively simple and straightforward.…”
Section: Resultssupporting
confidence: 86%
“…Those Au–thiolate NCs having highly dense thiolated ligands and QY > 10% mostly are emitted at 600–700 nm, ,,, consistent with our Au NCs/–[Cys–Au­(I)] n – supramolecules (630 nm). Compared to the employed organic solvent, mixed ligands, ligand exchange, host–guest recognition, ultrasound- or light irradiation-treatment to obtain dense thiolated ligands on Au NCs for boosting the QY of Au NCs, ,,, our one-pot synthesis of highly photoluminescent Au NCs/–[Cys–Au­(I)] n – supramolecules is relatively simple and straightforward. In addition, good batch-to-batch reproducibility (relative standard deviations (RSD) < 5% from 5 batches) was obtained on the preparation of highly photoluminescent Au NCs/–[Cys–Au­(I)] n – supramolecules on the basis of their PL intensity.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1 were used to evaluate the radiative lifetime (τ rad ) which explains the lifetime component in the absence of nonradiative decay pathway. Technically, B ‐NCs and B ‐gel should yield similar τ rad if the QY enhancement is solely exclusive of collision quenchers ,. In our case, we observed a significant difference in the τ rad value (Table ).…”
Section: Resultsmentioning
confidence: 44%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Luminescent metal nanoclusters are of particular interest owing to their unique properties, including their high stability, low toxicity, large Stokes shi, and long luminescence lifetime, and thus such nanoclusters have attracted signicant research interest in recent years. [13][14][15][16][17][18][19][20][21][22][23][24] A major effort in current research on luminescent nanoclusters protected by thiolates is focused on the development of effective strategies to enhance their luminescence. To improve the quantum yield of photoluminescence (PL), it is of paramount importance to understand the PL mechanism and, in particular, the structural basis.…”
Section: Introductionmentioning
confidence: 99%